2011
DOI: 10.1177/1362168811412881
|View full text |Cite
|
Sign up to set email alerts
|

‘We teach plastic lessons to please them’: The influence of supervision on the practice of English language student teachers in Kenya

Abstract: This article analyses the process of supervision by teacher educators and its influence on English language student teachers during a practicum in Kenya. The student teachers were enrolled in a four-year Bachelor of Education course for teaching English at secondary school level. Drawing on the perspectives of teacher educators, co-operating teachers and student teachers, this analysis suggests that supervision was brief and un-coordinated and that the feedback student teachers received was mainly evaluative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 24 publications
(26 reference statements)
2
23
0
Order By: Relevance
“…Ten articles were based on behaviourism: Werts, Wolery, Holcombe, and Gast (1995), Lee (2002), Ferreira, Moore, andMellish (2007), Goodman, Brady, Duffy, Scott, and Pollard (2008), Rodriguez, Loman, and Horner (2009), Auld, Belfiore, and Scheeler (2010), Scheeler, Congdon, and Stansbery (2010), Duchaine, Jolivette, and Fredrick (2011), Ochieng' Ong'ondo and Borg (2011), and Scheeler, McKinnon, and Stout (2012.…”
Section: Data-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles were based on behaviourism: Werts, Wolery, Holcombe, and Gast (1995), Lee (2002), Ferreira, Moore, andMellish (2007), Goodman, Brady, Duffy, Scott, and Pollard (2008), Rodriguez, Loman, and Horner (2009), Auld, Belfiore, and Scheeler (2010), Scheeler, Congdon, and Stansbery (2010), Duchaine, Jolivette, and Fredrick (2011), Ochieng' Ong'ondo and Borg (2011), and Scheeler, McKinnon, and Stout (2012.…”
Section: Data-analysismentioning
confidence: 99%
“…Table 2 shows the task-related characteristics. It is suggested that feedback should be task-or goal-related (Black & Wiliam, 1998;Brinko, 1993;Ochieng' Ong'ondo and Borg, 2011;Sadler, 1989;Shute, 2008). Brinko (1993), reasoning from the social cultural theory, proposed that feedback should be directed at behaviour rather than on the receiver.…”
Section: Feedback Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two challenges have emerged out of the developmental perspective on the TESOL practicum. One is the quality of supervision by teacher educators (Bailey, 2006;Farrell, 2007Farrell, , 2008bOchieng'Ong'ondo & Borg, 2011;Tang, 2003;Youngs & Bird, 2010) and the other is how to make the practicum a real learning opportunity for student teachers' professional growth (Richards, 1998).…”
Section: Challenges Of the Tesol Practicummentioning
confidence: 99%
“…Unfortunately, supervision of preservice teachers has been practiced predominantly through observation and feedback (Jacobs et al, 2014). Many conceive of supervision as a detached supervisor attending to the technical aspects of observing preservice teachers' behavior and providing corrective feedback (Basmadjian, 2011;Ochieng' Ong'ondo & Borg, 2011;Rathel, Drasgow, & Christle, 2008;Rock, Gregg, Gable, Zigmond, Blanks, Howard, & Bullock, 2012;Scheeler, McAfee, Ruhl, & Lee, 2006). These conceptions are problematic in that they fail to recognize the pedagogical potential of supervision.…”
Section: Resultsmentioning
confidence: 99%